Efficacy and safety of topical application of 45% hydrogen peroxide solution in the treatment of common warts - Salloum, Hanan Moein; Khaddam, Jamal; Alkhair, Abdallah (Journal of medical and pharmaceutical sciences, 2022)
Objective: The study aimed to evaluate the effectiveness and safety of hydrogen peroxide topical solution, 45% (HP45) for treatment common warts. Patients and Methods: A Prospective study (Before& After) conducted for the period one year (January 2020- January 2021) at Tishreen University Hospital in Lattakia- Syria. 35 patients with common warts who received treatment with HP45 were included in the study. Results: The median age was 21years, 51.4% of patients were females. Most common sites of warts involvement were dorsum of the hands (44.6%), followed by palm of hands (41.3%). A statistically significantly reduction in mean warts size was occurred at the end of treatment (0.2±0.18 vs. 0.62±0.6, p:0.0001). Complete clearance was achieved in 51.2% of patients, most of these cases were in the last session. The best response to the treatment was in warts located on the dorsum of hands, with size less than 1 cm and duration of disease less than one year. Regarding of side effects, itching and stinging were more frequently seen, followed by edema. Conclusion: Topical application of HP45 was effective in removal of common warts. Except of itching and stinging, serious side effects not occurred.